Psychometric properties of the Burnout Assessment Tool - General version in nursing workers - Lacir José Santin Júnior; Bianca Gonzalez Martins; Juliana Alvares Duarte Bonini Campos; Ana Claudia Souza Vazquez; Maria Helena Palucci Marziale; Isabel Amelia Costa Mendes; Neyson Pinheiro Freire; Wilmar B. Schaufeli; Hans De Witte; Fernanda Ludmilla Rossi Rocha (Revista Latino-Americana de Enfermagem)
Objective: to analyze the validity evidence of the BAT – General version in a sample of Brazilian nursing workers. Method: a cross-sectional study design with non-probability sampling method was used among 3594 Brazilian nursing workers. The validity evidence was assessed by means of analysis based on the internal structure, on the relations to external variables, and on response process of the items. Results: the factor models of the BAT – General version showed goodness-of-fit to the data. However, the complete factor model enabled a better understanding of burnout syndrome in the sample. It was attested the BAT – General version dimensions were positively correlated with depression, anxiety and stress symptoms and negatively correlated with job satisfaction and satisfaction with life. The validity evidence analysis based on response process of the items revealed that BAT – General version works properly both in the group of nursing workers who reported having emotional or psychological health problems and in the group who denied these problems. Conclusion: the results provided robust validity evidence of the BAT – General version in Brazilian nursing workers.